2006
DOI: 10.1530/eje.1.02271
|View full text |Cite
|
Sign up to set email alerts
|

Early epitope- and isotype-specific humoral immune responses to GAD65 in young children with genetic susceptibility to type 1 diabetes

Abstract: Objective: The pattern of the humoral immunity to disease-associated autoantigens may reflect the severity of the autoimmune disease process. The purpose of this study was to delineate the maturation of the humoral immunity to one of the main autoantigens in type 1 diabetes (T1D), glutamic acid decarboxylase (GAD65). Design and methods: Serum samples were obtained for the detection of epitope-and isotype-specific antibodies sequentially with short intervals from 36 young children with HLA-conferred genetic sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 35 publications
2
20
0
Order By: Relevance
“…Since the humoral immune system was already attacking multiple autoantigens, namely GAD, insulin, and IA-2 in the broad responders, we expected this phenomenon to be reflected by a broad activation also at the level of epitope and isotype specificity to a single antigen. Such a hypothesis is in line with the epitope spreading seen in prediabetes and the isotype switching/spreading reported for both GAD (19) and IA-2 (9, 20) in preclinical T1D. To our surprise, the isotype-specific response to IA-2 turned out to be broader among the IA-2-restrictive responders.…”
Section: Discussionsupporting
confidence: 88%
“…Since the humoral immune system was already attacking multiple autoantigens, namely GAD, insulin, and IA-2 in the broad responders, we expected this phenomenon to be reflected by a broad activation also at the level of epitope and isotype specificity to a single antigen. Such a hypothesis is in line with the epitope spreading seen in prediabetes and the isotype switching/spreading reported for both GAD (19) and IA-2 (9, 20) in preclinical T1D. To our surprise, the isotype-specific response to IA-2 turned out to be broader among the IA-2-restrictive responders.…”
Section: Discussionsupporting
confidence: 88%
“…These changes were evident at the same time point where the highest levels of GADA induced by the treatment were observed [15]. In the Prediction and Prevention study in Finland, emergence of GADA of the IgG4 subclass was observed in genetically susceptible children who remained non-diabetic [32]. Moreover, higher GADA of the IgG4 subclass were observed in LADA as compared to type 1 diabetes patients, which was interpreted as an indication of a more balanced immune response in the pancreatic tissue [33].…”
Section: Discussionmentioning
confidence: 84%
“…In addition, GADA IgG1–4 subclass distribution remained similar in all groups until 9 months, when the proportion of IgG4 in the 4D group drastically increased in parallel to a decrease of IgG1, supporting the notion of an enhanced humoral Th2-like response by additional GAD-alum doses. Previous studies have shown that higher levels of GADA IgG4 were associated with slower progression to clinical onset of disease in at-risk individuals (24,25). Furthermore, immunization with insulin promoted IgG4 in type 1 diabetic patients, an event interpreted to be associated with a Th2-like response (26).…”
Section: Discussionmentioning
confidence: 96%